Celebration for orchestra - Chen, Yi 1953- (Presser, 2014)
A bright and cheery, vividly energetic piece for orchestra
"Transposed score"--Page 3. - Includes program notes in English. - Duration: approximately 5 minutes
Keywords: Orchestral music / Scores